"Concealed cardiomyopathy" is an important cause of autopsy-inconclusive sudden cardiac death and diagnosis impacts care of surviving relatives. (3rd October 2022) - Isbister, J C; Nowak, N; Yeates, L; Singer, E S; Sy, R W; Ingles, J; Raju, H; Bagnall, R; Semsarian, C
Abstract: Background: Genetic testing following sudden cardiac death (SCD) is currently guided by autopsy findings, despite the inherent challenges of autopsy examination and mounting evidence that malignant arrhythmia may occur prior to structural changes in inherited cardiomyopathy, so-called "concealed cardiomyopathy" (CCM). Purpose: To identify the spectrum of genes implicated in autopsy-inconclusive SCD and describe the importance of identifying CCM for the ongoing care of SCD families. Methods: Using a standardised framework for adjudication, autopsy-inconclusive SCD cases were identified as having a structurally normal heart or sub-diagnostic findings of uncertain significance on autopsy. Genetic variants were classified for pathogenicity using the American College of Medical Genetics and Genomics guidelines. Family follow-up was performed where possible. Results: Twenty disease-causing variants were identified among 91 autopsy-inconclusive SCD cases (mean age 25.4±10.7 years) with a similar rate regardless of the presence or absence of sub-diagnostic findings (25.5% vs 18.2%, p=0.40). Cardiomyopathy-associated genes harboured 70% of clinically-actionable variants and were overrepresented in cases with sub-diagnostic structural changes at autopsy, accounting for 11 out of 12 disease-causing variants in this group (79% vs 21%, p=0.038, Figure 1, panel A). Variants in arrhythmogenic cardiomyopathy genes were the most common cause of CCM (9/14 CCM cases, Figure 1, panel B). Nearly two-thirds of genotype-positive relatives had an observable phenotype either on initial assessment or during subsequent follow-up. Twenty-seven genotype-negative first-degree relatives were released from ongoing screening. Conclusion: The current paradigm of phenotype-directed genetic testing following SCD risks under recognition of CCM. Comprehensive evaluation of the decedent should include assessment of genes implicated in both cardiomyopathy and primary arrhythmias to improve diagnosis of CCM and optimise care for families. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Heart Foundation of Australia and National Health and Medical Research CouncilNew South Wales Health